Communication Strategy on Smart Education in Building Trust of Parents of Children with Disabilities in Parepare City - fitriani; Muhammad Qadaruddin; Nurhikmah; Ramli; Iskandar (Palita: Journal of Social Religion Research, 2025)
Abstract This study discusses the communication strategies implemented by Smart Education in building trust among parents of children with disabilities in Parepare City. This study departs from the need to understand how trust among parents of children with disabilities can be built, because children's limitations make parents tend to be more cautious in entrusting assistance to others. Therefore , the importance of appropriate communication strategies by educational institutions in creating a sense of security and trust. This study is a descriptive qualitative study that describes data obtained in the field related to the procedures for directors and tutors to build trust among parents of children with disabilities in Parepare City. Data collection was carried out through interviews, as well as through books and other literature. These literatures were used as theoretical foundations and references to strengthen the analysis of data obtained from the field. This study shows that Smart Education builds trust among parents of children with disabilities through five main approaches:empathetic communication, participatory communication, humanistic communication, the ability to overcome information challenges, and specific strategies for building trust. Empathy is demonstrated through emotional understanding of parents, participation through their active involvement in the educational process, and humanistic communication through warm and equal supported relationships​ by the theories of Symbolic Interactionism and Communicator Credibility, these findings confirm that communication based on empathy, participation, and honesty not only strengthens parental trust but also contributes to more effective inclusive education practices . Keywords : Communication Strategy , Parental Trust, Children With Disabilities